Effect of Rice Bran Oil Addition on the Physicochemical, Microstructural, and Antioxidant Properties of Chicken Corned Meat - Ahmed Hafizd Athththoriq; Agus Susilo; Herly Evanuarini; Dedes Amertaningtyas; Khothibul Umam Al Awwaly (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to evaluate the effect of rice bran oil (RBO) supplementation on the physicochemical properties, microstructure, and oxidative stability of chicken-based meat emulsion products. RBO is rich in natural antioxidants such as γ-oryzanol and tocopherols, which may enhance product quality. A Completely Randomized Design (CRD) was used with four treatments (0%, 6%, 8%, and 10% RBO) and six replications. Parameters measured included pH, peroxide value (PV), color values (L*, a*, b*), microstructure (SEM), moisture, ash, fat, protein, carbohydrate, water activity (Aw), free fatty acids (FFA), and total acidity. The addition of RBO significantly (P<0.01) reduced PV, FFA, and total acidity, indicating improved oxidative stability. It also enhanced protein content, microstructural integrity, and textural properties. Although total fat content increased, the proportion of unsaturated fatty acids improved the lipid profile. Reduction in water activity suggested enhanced shelf stability. These findings demonstrate that Adding 10% rice bran oil (RBO) to chicken meat emulsions improved emulsion stability, reduced lipid oxidation and free fatty acids, enhanced protein retention, and improved microstructure.